Hispanic Millennial Ideology: Surprisingly, No Liberal "Monolith" Among College Students. Issue 3 (August 2019) - Greene, William; Kim, Mi-son
The goal of this study is to analyze the ideological positions of Hispanic college students in the U.S. Rio Grande Valley (RGV). Building on Feldman and Johnston's work, where they argue that a unidimensional model of political ideology provides an incomplete basis for study, we employ two dimensions to account for domestic policy preference. The core of the study is a taxonomic analysis of a survey of RGV college students taking government courses, where we find that the political beliefs of Hispanic millennials trend significantly more conservative and, especially, libertarian than expected. Possible implications for the future include a realignment of Hispanics with the Republican Party, a shift in a more libertarian direction within the Democratic Party itself, or an increase in younger Hispanics' proclivity for independence from the two major parties. Our findings conform to Feldman and Johnston's argument that the economic and social dimensions of political ideology are separate and distinct, making it essential that researchers analyze both dimensions in order to have an accurate and comprehensive understanding of individuals' political ideology. In addition, using recent American National Election Studies (ANES) data sets, we compare how our samples are different from the general U.S. population, employing a principal component analysis (PCA).